Dialogue and Participation: Experience in the Construction of Knowledge With Women in Situations of Violence (Revista Brasileira de Pesquisa em Educação em Ciências, 2025)
The article highlights the importance of qualified listening and creating a safe environment during interviews with women experiencing violence, based on the interviewee’s experience. The goal is to reflect on how these practices ensure respect and validation of participants’ voices, fostering meaningful dialogue between researchers and vulnerable communities. The research adopts a qualitative and exploratory approach, characterized as a case study and grounded in black feminist epistemology, which prioritizes the valuing personal experiences and maintaining an ethical commitment to the dignity of the participants. The results indicate that a safe environment facilitates more open accounts of violence. Additionally, they reinforce the need for researchers to go beyond academia, actively listening to and understanding these stories with respect. The study emphasizes the urgency of concrete actions that value the experiences of women facing violence, promoting an ethical and socially responsible commitment to knowledge production and the defense of dignity and social justice.